Representing SSR molecular marker profiles using concepts from Andean khipus - Simon, R.; Carhuapoma, Pablo; Hualla, V.; Ghislain, M.; Mendiburu, F. de; Gómez, R.; Zorrilla, C.; Roca, W.; Haan, Stef de; Bonierbale, Merideth W. (PeerJ, 2014)
Genebanks increasingly use molecular markers for routine characterization of ex-situ collections and farmer managed diversity. The International Potato Center presently uses a SSR marker-kit to create molecular profiles for potato accessions. We identified a need for a compact graphical representation that allows comparative presentation of molecular diversity and accession characteristics - thereby permitting biologists and collection curators to have a simple means to interpret molecular data. Inspired by the ancient Andean qipus we devised a graph that standardizes representation while leaving room for updates of the marker kit and the collection of accessions. The molecular khipu permits combining and annotating a set of SSR loci with allele frequency and allele size distribution information. The design is flexible to incorporate updates on genetic diversity information. Graphical means facilitate reading of allele diversity information. As a compact graphical view it facilitates information storage and exchange. The SSR khipu will be useful to other genebanks and breeders. Software to create graphics in single or batch mode is available as R package ’khipu’.